488 GRIP STRENGTH FROM MIDLIFE AS AN INDICATOR OF LATER-LIFE COGNITION AND BRAIN HEALTH: EVIDENCE FROM A BRITISH BIRTH COHORT. (14th June 2021) - Dercon, Q; Nicholas, J; James, S-N; Schott, J; Richards, M
Abstract: Introduction: Grip strength is an objective measure of physical function with potential predictive value for health in ageing populations. We aimed to assess whether levels and changes in grip strength from midlife predicted later-life brain health and cognition. Methods: 446 participants in an ongoing British birth cohort study, the MRC National Survey of Health and Development (NSHD), had their maximum grip strength measured at ages 53, 60–64, and 69, and underwent neuroimaging as part of its neuroscience sub-study, Insight 46, at 69–71. A group-based trajectory model identified latent groups of individuals in the whole NSHD cohort with below- and above-average grip strength over time, plus a reference group. Trajectory group membership, plus standardised grip strength levels and change from age 53, were each related to MRI-derived measures of whole-brain volume (WBV) and white-matter hyperintensity volume (WMHV), plus several cognitive tests. Models were adjusted for sex, body size, head size (where appropriate), sociodemographics, and behavioural and vascular risk factors. Results: Consistently below-average grip strength from midlife was associated with lower WBV and non-verbal reasoning ability at age 69–71 (e.g. low group WBV vs. reference group β = −13.38 cm^3; 95% CI = (−24.12 cm^3, −2.64 cm^3); p = 0.015). There was some accompanying evidence that above-average maximum grip strength showed a positive association with WBV, which was more pronounced in female participants (high group female WBV vs. reference group β = 18.30 cm^3; 95% CI = (1.34 cm^3, 35.29 cm^3); p = 0.034). Steeper than average declines in grip strength between 53 and 69 were additionally weakly associated with an estimated 10% higher WMHV at age 69–71 (β = 1.10, 95% CI = (1.00, 1.22); p = 0.053). Conclusion: This study provides preliminary evidence that tests of maximum grip strength may have value in predicting brain health. Future work should assess how these observed differences relate to later-life negative health outcomes, and whether changes in grip strength reflect concurrent changes in brain structure and connectivity.